Beginner's guidto digital painting in Photoshop. (Worcester : 3DTotal Publishing, 2015)
Beginner's Guide to Digital Painting: Characters is a comprehensive guide for artists wishing to create convincing and detailed characters. It features established artists such as Charlie Bowater (concept artist at Atomhawk) and Derek Stenning (freelance concept artist and illustrator, with clients such as Marvel Entertainment and Nintendo) who share their industry experiences by covering such aspects as posing characters, choosing the correct costumes, conveying emotions, and creating suitable moods. Conclusive step-by-step instructions make this an invaluable resource for artists looking to learn new skills, as well as those pursuing the next level.
Keywords: Adobe Photoshop; Computer graphics